Powdered Yoghurt Probiotic Quality Produced by Foam-Mat Drying Method with different Drying Temperature and Albumen Level - Sukarno, Ari Surya (2014)
The study aimes to determine the effect of different drying temperature and albumen level on the quality of powdered yoghurt probiotic produced by foam-mat drying method. Yoghurt was produced by 5% Streptococcus thermophilus and Lactobacillus bulgaricus starter with ratio 1:1, and added 2% Lactobacillus casei as probiotic. The drying temperature of yoghurt was 50, 60, and 70ºC, whereas the level of albumen was 0, 10, and 15%. The analyzed of powder yoghurt quality include: 1) microbiological quality (total of lactic acid bacteria and probiotic), 2) chemical quality (protein, moisture, pH, and acidity), and 3) physical quality (solubilty). The data of yoghurt quality was analyzed statistically by two way ANOVA 3x3. The results showed that total lactic acid bacteria (LAB) and probiotic of powdered yogurt with drying temperature of 70o C were lower (P<0.05) than temperature 60 and 50o C, whereas the level of albumen had no effect on microbiological quality. Drying temperature of 70o C could decrease the total lactic acid bacteria (LAB) and probiotic, moisture content, solubility and increase the pH of powdered yoghurt. The level of albumen had no effect on moisture content, solubility, acidity, and pH, but could affect significantly on the protein content of powdered yoghurt. In conclusion, powdered yoghurt probiotic should be produced by drying temperature of 60o C and 10% albumen level. Keywords: Yoghurt powder quality, Probiotic, Foam-mat drying, Albumen.